Competitive indicators from Colombia and U.S. rice production - Chica L., Jaqueline; Tirado O., Yeimy Carolina; Barreto O., Joan Manuel (Revista de Ciencias Agrícolas, 2016)
Colombia has been deepen its integration into the world market through free trade agreements with different countries, for the last twenty years. Despite its vulnerability, the agricultural sector has been linked to these agreements. Rice, is the third most important crop in the country and it was included in the agreement with the United States. Since then, its prevalence as a mayor crop is questioned. The current study evaluated the competitiveness of the Colombian and United States rice sector, through revealed competitiveness and quasi-rents indicators; identifying the influence of economic and non-economic factors, with the aim to evaluate the impact of the Free Trade Agreement in the Colombian rice production and its capability of sustaining by itself in the national market. The Colombian revealed competitiveness indicators show negative and close to zero values, in other words, null levels of competitiveness; in contrast the USA competitiveness levels were close to one, showing its strength as a competitor in the international arena. Similarly, the quasi rent indicator revealed a higher competitiveness of USA’s rice sector. This is explained by the use of very efficient and advanced production technology, political instruments involving investment in post-production infrastructure and transportation, and direct subsidies for the producers. The Free Trade Agreement with the USA could threaten the national food security if low competitiveness of the rice producers is maintained, since the increase of the international prices negatively influence rice supply and accessibility.